Sustainable development of education as inclusive economic growth basis - Oleksandr Chaikin (Вісник: Київський інститут бізнесу та технологій, 2021)
The article considers the issue of sustainable development of education as a basis for inclusive economic growth. We present the analytical assessment of current and target values ​​of the leading indicators of The Sustainable Development Goal 4 "Quality Education" (SDG 4). The main characteristics of dynamic processes of inclusive development in conditions of sustainable economic growth are given. The tasks and indicators of the CSB in education are presented, which are an informational, statistical, and analytical basis for monitoring the implementation of sustainable development in the context of ensuring inclusive growth of economic systems. The main stages of formation and integration of principles, values ​​, and practical measures of sustainable development of education of all levels and types are presented. Ukraine traditionally has a high level of school enrollment and basic adult literacy. Still, there are some local gaps and imbalances in access to the Internet, computer and software, formal and non-formal education. Based on the analysis of current and target values ​​of the main indicators of achieving SDG 4, the last decade has seen some positive changes. However, the armed confrontation only increased social tensions and population stratification, exacerbated by the global pandemic, so achievements were somewhat eliminated due to the systematic crisis. The quality of logistics is relevant for educational institutions, especially in rural areas, and significantly affects the economic, social, and territorial cohesion of newly created communities, limiting/expanding opportunities for inclusive growth. It is substantiated that increasing the cohesion and capacity of local communities to effectively solve a significant part of the existing problems of spatial development strengthens the inclusiveness of economic development. Systematic reform of the education sector is proposed, envisages updating education standards and bringing them to international levels to ensure equal access to such a social service as education for all citizens.